CHARACTERISTICS OF DENGUE FEVER IN A LARGE PUBLIC HOSPITAL, JEDDAH, SAUDI ARABIA - Ayyub, Muhammad; Khazindar, Adel M; Lubbad, Eman H; Barlas, Shahid; Alfi, Adnaan Y; Ukayli, Sawsan Al- (Journal of Ayub Medical College Abbottabad, 2006)
Background: This study aims to determine demographic, clinical and laboratory profile along with disease outcome of all confirmed cases of dengue fever (DF) and dengue hemorrhagic fever (DHF) admitted in King Abdulaziz Hospital & Oncology Center, Jeddah, Saudi Arabia. We also want to highlight the significance of implementing a well targeted community based disease prevention program. Methods: All patients admitted from May 2004 till April 2005 with a suspected diagnosis of DF and DHF were followed. All cases confirmed by a positive serology (IgM alone or IgM and IgG) to dengue fever were studied in detail to determine age, gender, ethnicity, monthly distribution, clinical and laboratory profile. Results: A total of 80 patients were admitted with a suspected diagnosis of DF. Among these, 39 (48.75%) patients were confirmed by positive serology to have the disease. Male to female ratio was 3.3:1. Their ages ranged from 2 to 60 years with a mean of 27.6 + 11.2. Twelve patients were Saudis, while the rest were non-Saudis coming from different countries in Asia, Africa and Middle East. Maximum number of patients (48.72%) was seen in the summer months of June, July and August. Commonest presentation was fever (100%), headache (48.72%), myalgias (66.7%) and vomiting (25.64%). Rash, hemorrhagic manifestations and positive tourniquet test were relatively uncommon. Only two patients fulfilled WHO criteria of DHF. Main hematological abnormalities were thrombocytopenia (79.49%) and leucopenia (48.72%). Significant elevation of PTT was observed in 25.64% of patients. Abnormal liver function tests with high transaminases were seen in about 66.7% of patients, whereas 33.33% of patients had significantly elevated creatine kinase. All patients improved clinically with improvement of chemical and hematological parameters. None of the patients died in this series. Conclusion: DF continues to be a significant health problem in Western region of Saudi Arabia. Large number of pilgrims coming from disease endemic areas all over the world facilitates the continued introduction of dengue virus with different strains. Fortunately there has been no serious outbreak of dengue fever in recent years. A sharp vigilance is required by concerned authorities to prevent and minimize any future outbreak. It is extremely important to implement and maintain an effective, sustainable and community based disease prevention program. Key Words: Dengue fever, Dengue hemorrhagic Fever, Headache, Rash, Thrombocytopenia